PENGARUH REVIEW PRODUK DAN KONTEN MARKETING PADA TIKTOK SHOP TERHADAP KEPUTUSAN PEMBELIAN SKINTIFIC PADA GENERASI Z DI KOTA PALANGKA RAYA - Bulan Putri, Marjuliansi; Nahan, Noorjaya; Ruzaini Abdi, Muhamad; Harjoni, Harjoni (Penerbit Lafadz Jaya, 2025)
The digital era has transformed social media platforms into transaction channels, including TikTok Shop which has become a popular e-commerce platform among Generation Z. This study aims to analyze the influence of product reviews and marketing content on TikTok Shop on Skintific purchase decisions among Generation Z in Palangka Raya City. The research used quantitative methods with survey techniques on respondents aged 17-28 years who actively use TikTok and are interested in skincare products. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results showed that product reviews have a positive and significant effect on purchase decisions. Marketing content has a greater and more dominant influence than product reviews. Simultaneously, both variables significantly influence and can explain most of the variation in purchase decisions. The findings show that Generation Z in Palangka Raya City is more influenced by visual and interactive marketing content compared to product reviews in making purchase decisions. This indicates the need to optimize integrated marketing content strategies to improve sales effectiveness on the TikTok Shop platform, particularly in reaching young consumers who have digital native characteristics.